(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Murals are one of the techniques of delineation, which was influenced by Hantine and Sassanian in fluencies. They been their independence in the Umayyad period to maturity in the Abbasid era. The Levant was one of the centers of creativity for these drawings implemented in a mosaic and frisco. The drawing are important documents in history,arecord of daily life and evidence of settlement.to know the properties of the wall paintings, it is necessary to study the drawings which were implemented in the mosaic and in Frisco. There fore, the focus was on important bulding that included the drawing in mosaic such as the Dome the Rock and theUmayyad mosquen and the khirbat al-mfjar palace. And the drawing in frisco such as Omra palase and palase of western Hier.